On the solution of the fully fuzzy Sylvester matrix equation. (2nd January 2020) - Keyanpour, Mohammad; Salkuyeh, Davod Khojasteh; Moosaei, Hossein; Ketabchi, Saeed
ABSTRACT: The aim of this paper is to propose a method for solving fully fuzzy Sylvester equation (FFSE) A X + X B = C, where A, B and C are fuzzy matrices. By using of α -cutting, FFSE is transformed to a generalized Sylvester matrix equation, and then to a crisp system of linear equations. Existence and uniqueness of a solution to this system are investigated. Two numerical examples are given to illustrate the proposed method.